Comparative study of pregnancy diagnosis in ewes (Ovis aries) using barium chloride and progesterone-kit (Bangladesh Veterinarian, 2022)
One hundred and twenty sheep were used to test a low-cost technique for early diagnosis of pregnancy in sheep from July 2017 to June 2018. Different age groups were randomly categorized under four groups (15 to 30 days, 31 to 45 days, 46 to 60 days & 61 to 75 days). One mL barium chloride (1, 1.5 & 2%) was mixed with one mL of urine and kept for 5 to 10 minutes at room temperature: precipitation indicated non-pregnant. Three to five drops of serum were added to Bovipreg kit (progesterone-based kit) and left at room temperature for 5 minutes. One red line was interpreted as negative and two red lines positive for pregnancy. Barium chloride solution gave 67 - 70.5% accuracy. The accuracy for progesterone-based early pregnancy diagnostic kit was 80 - 85%. Progesterone-based early pregnancy diagnostic kit is much more accurate.The Bangladesh Veterinarian (2020) 37(1 - 2): 36-41